UPAYA PENCEGAHAN CEDERA OLAHRAGA SEBELUM DAN SELAMA PERTANDINGAN PADA UKM OLAHRAGA UMPP TAHUN AKADEMIK 2019/2020 - -, mega (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2021)
Every person when exercising is always faced with the possibility of an injury and this injury can interfere with daily activities and can even be so fatal that he cannot perform activities at all for weeks. The cause of sports injuries is trauma (forced ruda) directly (hitting soft tissues, namely: skin, muscles, tendons and ligaments) or indirectly (hitting hard tissues, namely bones). This trauma can occur due to 2 factors, namely the Overuse factor (overuse syndrome) and environmental factors (temperature, weather, altitude, and depth). In general, many sports injuries are caused by overuse factors. According to Wibowo (1995) in Jamal (2009: 1) "Sports injuries are all kinds of injuries that arise, both during training and during sports (matches) or after matches". Commonly affected are bones, muscles, tendons and ligaments. Thus knowledge about sports injuries is useful for learning how sports injuries can treat / help / overcome (curative) and preventive action (prevention). An effective way of dealing with injuries is to understand the different types of injuries and recognize how our bodies respond to them. That is also, we can understand the body so that we can know what to do to prevent injury. To detect an injury so that it does not get worse, what is done is to be given professional treatment.